COVID-19 and the law : disruption, impact and legacy - Cohen, I. Glenn; Gluck, Abbe R.; Kraschel, Katherine L., 1983-; Shachar, Carmel, 1985- (Cambridge University Press, 2024)
The COVID-19 pandemic has had an enduring effect across the entire spectrum of law and policy, in areas ranging from health equity and racial justice, to constitutional law, the law of prisons, federal benefit programs, election law and much more. This collection provides a critical reflection on what changes the pandemic has already introduced, and what its legacy may be. Chapters evaluate how healthcare and government institutions have succeeded and failed during this global 'stress test,' and explore how the US and the world will move forward to ensure we are better prepared for future pandemics. This timely volume identifies the right questions to ask as we take stock of pandemic realities and provides guidance for the many stakeholders of COVID-19's legal legacy. This book is also available as Open Access on Cambridge Core.